TEACHING AND LEARNING TO READ AND WRITE AS A HUMANIZING PROCESS - Miller, Stela [UNESP] (Universidade Estadual de Londrina, 2020)
This article aims to reflect on teaching and learning to read and write as a humanizing process. The bases for this reflection are the assumptions of the Cultural-Historical Theory, which defends the socio-historical-cultural conditionality of man, of the Activity Theory, which proposes the activity as fundamental in the constitution of social subjects and, also, of bakhtinian thought about enunciation. Because of this reflection, we affirm that the best way to teach and learn the mother tongue is to think, plan and organize it in order to promote in the student the ability to read constituting a responsive understanding for statements and write producing statements addressed to real readers. Reading and writing projects are suitable for this purpose when developed through activities whose object is the discursive enunciation, and the study actions focus on the reading of statements produced socially and historically, and the production of statements in their social function. Thus, the work with reading and written production is no longer merely formal and becomes an instrument of humanization of the student, who will be able to gain an understanding of others' statements and the ability to produce statements for others
O ENSINO E A APRENDIZAGEM DA LEITURA E DA ESCRITA COMO UM PROCESSO HUMANIZADOR
Keywords: Activity; Education; Humanization; Mother tongue; Reading and writing